2009
DOI: 10.1097/ncc.0b013e3181982d7b
|View full text |Cite
|
Sign up to set email alerts
|

A Different Approach to Breast Self-Examination Education

Abstract: Breast cancer is a common cancer among women, and early detection is important for breast cancer mortality and morbidity. The aim of this study was to determine the effects of daughters teaching their mothers about breast self-examination (BSE) and its health beliefs. In the study's first stage, 168 university students were trained by the School of Health students about BSE through group training methods. Then, these trained university students were asked to train their mothers about BSE. Data were collected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In comparison, this finding is not significant with the number of studies from several other countries. [ 6 11 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, this finding is not significant with the number of studies from several other countries. [ 6 11 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, some studies have shown that majority of breast tumors are initially detected by patients by touch (17). It should be noted that, based on previous published articles, offering training on breast cancer influences women's health beliefs as well (12,16,18); therefore, it seems that improving students' health beliefs may lead to regular BSE practices.…”
Section: Discussionmentioning
confidence: 99%
“…One’s risk of dying from breast cancer is reduced by routine screening [ 13 ]. Three tools are suggested for BC screening: mammography, clinical breast examinations (CBEs) by a doctor, and breast self-examinations (BSEs) [ 14 ]. Breast self-examination is a quick, easy, private, low-cost, non-invasive process that does not require any specific materials or tools.…”
Section: Introductionmentioning
confidence: 99%